Organizational predators of disability sports participation of secondary school students with special needs in Ibadan, Nigeria - Samson, Oladipupo Oluwaseyi; Adegbola, Adegbesan Olufemi; Deborah, Alamu Jesuferanmi; Mobolaji, Ajisafe Paul (Journal of Sports Research, 2024)
Active participation of students with disability in adapted sport is dependent on several organizational predators. The purpose of this study is to examine how organizational predators independently and jointly contribute to disability sport participation among secondary school students with special needs in Ibadan, Nigeria. The methodology featured Chain-Referral (snowball) to identify stakeholders, coaches, organizers and teachers involved in organizing disability sport for students with disability and probability sampling technique to choose the schools to be visited. The findings revealed that Strategic planning (ß=0.289, t=2.816, p=0.008), logistics (ß=0.612, t=7.103, p=0.000), interest of coaches (ß=0.536, t=7.795, p=0.000) and knowledge of organizing personnel (ß=0.500, t=7.836, p=0.000) were independently tested significant on disability sport participation while network capacity (ß=0.171, t=1.772, p=0.085), funding sources (ß=0.082, t=1.360, p=0.182) and sport infrastructure (ß=0.111, t=1.948, p=0.059) were not independently tested significant on disability sport participation. Also, there is a composite joint contribution of strategic planning, network capacity, infrastructure, funding, logistics, interest of coaches, and knowledge of organizing personnel on disability sports participation among secondary school students with special needs in Ibadan, Nigeria (F(7,39)=100.210, p=0.00). The result also generated a coefficient multiple regression of R=0.977 and R2 =0.955; implying that about 95.5% of variance was accounted for by the independent variable. Strategic planning, logistics, interest of coaches, and knowledge of organizing personnel individually and collectively showed a positive contribution to disability sport participation, hence, there is a need to consider them on the subject of disability sport participation in schools of individuals with special needs in Ibadan, Nigeria.